A case of albendazole and niclosamide resistant Taenia saginata infection - Mohanty, Aroop; Singh, T. Shantikumar; Bhutia, Tshering Ongmu; Gupta, Pratima; Gupta, Priyanka (International Journal of Research in Medical Sciences, 2017)
Taenia saginata infection is an important food-borne parasitic zoonosis which is endemic in countries where majority of people eat raw or inadequately cooked beef. The infection is rare in India except in Jammu Kashmir and Northeast states, India. Majority of taeniasis patients are asymptomatic, few may present with a variety of abdominal symptoms and rarely hepatobiliary complications. Diagnosis is made commonly by finding proglottids and or eggs in the faeces. Here we report a chronic and uncomplicated case of saginata taeniasis resistant to niclosamide and albendazole but responded to a single dosage of praziquantel 15 mg per Kg body weight.